Removing inactive NRTIs in a salvage regimen is safe, maintains virological suppression and reduces treatment costs: results from the VERITAS study (TMC114HIV4054). Issue 3 (May 2015) - Trottier, Benoit; Galanakis, Chrissi; Longpré, Danièle; Dion, Harold; Vézina, Sylvie; Lavoie, Stéphane; Boissonnault, Michel; Costiniuk, Cecilia; Jenabian, Mohammad-Ali; Machouf, Nimâ; Thomas, Réjean
Abstract : Background: Despite the benefit of maintaining inactive Nucleotide/side reverse transcriptase inhibitors (NRTIs) in salvage regimens, they are associated with increased toxicity and treatment costs. Current evidence suggests that NRTI-sparing regimens in patients failing ART are non-inferior to NRTI-including regimens. This study aimed to evaluate the impact of removing at least one inactive NRTI on virologic, safety, and financial outcomes. Methods: Drug-resistant, virologically suppressed patients with CD4 >250 cells/ml on a stable regimen of four or more antiretrovirals (ARVs) were enrolled in a 48-week prospective, open-label pilot trial. One inactive NRTI was removed at baseline. Patients taking over five ARVs had a second inactive NRTI removed at 24 weeks. Viral load, CD4 count, and adverse events were assessed at baseline, 24, and 48 weeks. Results: Thirty-one male patients participated. Twenty-nine (94%) patients had lamivudine (3TC) or emtricitabine (FTC) removed and four patients had an additional NRTI removed. One patient was excluded at week 26 for discontinuing an active NRTI. All patients maintained undetectable viral loads at weeks 24 (100%) and 48 [PP = 100%; Intent-to-treat (ITT) = 97%]. At 48 weeks, patients had a median gain of 20 CD4 (IQR: − 50, +133; mean +39) compared to baseline. Three patients exhibited Grade III bilirubin elevation (two Grade II and one Grade III at baseline), which returned to baseline levels. No serious adverse events were observed. Removal of one or two ARVs equated to a mean annual savings of $3319 CDN (11%) and $8630 CDN (24%), respectively. Conclusion: Removing inactive NRTIs in patients with a controlled viral load appears to be safe, maintains virological suppression, and reduces treatment costs.